1995
DOI: 10.1002/job.4030160306
|View full text |Cite
|
Sign up to set email alerts
|

Family Support Inventory for Workers: A new measure of perceived social support from family members

Abstract: A measure of family social support for workers was developed, and initial investigations of its psychometric characteristics were conducted. Data from several samples endorse the internal consistency of the support dimensions of emotional sustenance and instrumental assistance, and confirmatory factor analysis findings reinforce the bidimensional structure of the instrument. Lack of a relationship with social desirability, correlations with life and job satisfactions, and gender differences in perceived instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
221
0
13

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 231 publications
(240 citation statements)
references
References 43 publications
6
221
0
13
Order By: Relevance
“…Sample items include: "I am often too tired at work because of things I do at home" and "I am preoccupied with my personal life while at work." King, Mattimore, King, and Adams' (1995) Family Support Inventory for Workers was used to measure family social support; it contains a 29-item emotional sustenance subscale and a 15-item instrumental assistance subscale. Sample items from the emotional sustenance subscale are "Someone in my family helps me feel better when I'm upset about my job" and "Members of my family always seem to make time for me if I need to discuss my work."…”
Section: Methodsmentioning
confidence: 99%
“…Sample items include: "I am often too tired at work because of things I do at home" and "I am preoccupied with my personal life while at work." King, Mattimore, King, and Adams' (1995) Family Support Inventory for Workers was used to measure family social support; it contains a 29-item emotional sustenance subscale and a 15-item instrumental assistance subscale. Sample items from the emotional sustenance subscale are "Someone in my family helps me feel better when I'm upset about my job" and "Members of my family always seem to make time for me if I need to discuss my work."…”
Section: Methodsmentioning
confidence: 99%
“…Thus, research has found that workplace social support is positively related to greater job satisfaction and training effectiveness, and the level of social support received from significant others, including top management, supervisors, peers, and subordinates, all have an influence on individuals (Chen et al, 2007;Harris et al, 2007). In addition to the social support an employee perceives as having in his/her work environment, Adams, King, and King (1996) uncovered the fact that higher levels of family emotional and instrumental social support are significantly associated with less family and work conflicts, less workplace stress (Noor, 2002), and further believe that a higher level of job satisfaction (King et al, 1995) would be the result. It is believed that social support from one's family can also positively influence their life at work (Wayne, Randel, & Stevens, 2006).…”
Section: Social Support Theorymentioning
confidence: 99%
“…One established measure of family support is the family support inventory for workers (King et al, 1995). It measures two dimensions: emotional sustenance and instrumental assistance.…”
Section: Personal Characteristicsmentioning
confidence: 99%